Effects of magnesium-poor and arbuscular mycorrhizae on mineral nutrient uptake and distribution of ‘Newhall’ navel orange and ‘Ponkan’ tangerine grafted on rootstock trifoliate orange - YANG Yan; HU Chengyin; CHEN Qiang; ZHANG Xiaoping; XIAO Jiaxin (浙江大学学报. 农业与生命科学版)
The effects of magnesium-poor (Mg-poor) and arbuscular mycorrhizal (AM) fungus Glomus versiforme treatments on boron (B), phosphorus (P), potassium (K) and calcium (Ca) concentrations of different plant parts were investigated in potted ‘Newhall’ navel orange［Citrus sinensis (L.) Osbeck cv. Newhall］and ‘Ponkan’ tangerine (Citrus reticulata Blanco cv. Ponkan) grafted on the rootstock trifoliate orange. The results showed that Mg-poor increased B and P concentrations in the basal leaves, and K and Ca concentrations in the upper leaves of ‘Newhall’, while decreased the concentrations of B in the basal leaves, K in the upper leaves, and P and Ca in the upper and basal leaves of ‘Ponkan’. Under the Mg-rich condition, AM fungus inoculation significantly increased B concentration and percentage in the upper leaves of ‘Newhall’, and B concentration and percentage in different plant parts (except for the upper leaf) of ‘Ponkan’. In addition, AM fungus inoculation significantly improved the concentrations of P and Ca in the scion and rootstock stems, and K and Ca in the basal leaves of ‘Newhall’, as well as K in different plant parts, P and Ca in the roots, and Ca in the upper and basal leaves of ‘Ponkan’. Under the Mg-poor condition, AM fungus inoculation significantly enhanced the concentrations of B (except for the upper leaf of ‘Newhall’), P (except for the basal leaf of ‘Newhall’), K (except for the basal leaf of ‘Ponkan’), and Ca (except for the root of ‘Ponkan’) in different plant parts of the two cultivars, especially in the ‘Newhall’. These results indicate that G. versiforme-inoculation can improve the absorption and transportation of B, P, K and Ca in ‘Newhall’ navel orange grafted on trifoliate orange exposed to Mg-poor soil in a greenhouse. It provides a scientific basis for balanced fertilization in citrus cultivation to overcome the yellowing symptoms of nutrient deficiency.